Perencanaan Desain Offshore Kontruksi Bawah Laut menggunakan Pengolahan Data Pemodelan Geofisika dengan Program Simulasi 3D Surfer - Edy Soesanto; Aly Rasyid; Hadi Suyanto (Fakultas Teknik Universitas Bhayangkara Jakarta Raya, 2022)
Underwater construction design planning is increasingly being developed as a 3D modeling simulation, because 3D simulation is expected to be able to make the initial plan for making a design framework. Surfer is one of the software that was created for the purpose of making contour maps and three-dimensional modeling based on existing grids and simplifying and accelerating data conversion activities into the form of contour maps and surface plots. One of the applications is Surfer in the field of Underwater Technology development is 3D modeling simulation and bathymetric contour map making, sediment layer modeling using SBP data and making current stick plots to determine circulation and current velocity and direction. In addition, Surfer can also display maps in 2D or 3D. on this occasion Surfer 16 software will be used to process marine acoustic data with X (Easting) data, Y (Northing) data and six Z layer depths, namely Z1-Z6, the data is processed in one step to make 2D and 3D models which are then will be interpreted as a simulation material for the initial planning of the underwater construction design.